Dynamic classification of the dairy cooperative sectors in the Ciego de Avila province, Cuba - Mart?nez-Melo, J.; Torres, Verena; Jord?n, Humberto; Guevara, G.; Hern?ndez, N.; Brunett, L.; Fontes, Dayam?; Mazorra, C.; Lezcano, Yohanka; Cubillas, Nieves (Cuban Journal of Agricultural Science, 2011)
The productive records of each cooperative sector in all the municipalities, from 2002 to 2009, were obtained for classifying dynamically each cooperative sector of the Ciego de Avila province, Cuba. The methods of principal components (PC) and clusters were combined to classify the cooperative sectors. The amount of animals, total milk yield, births and deaths, explaining between 51.3 and 65.7 % of the total variance, were included in the first PC. Four groups of cooperative sectors were obtained for the years classified. In 2009, group 1 only included the cooperative sectors where producers work together: no land owners (C1) and land owners with only 107207 L a year (C2). Groups 2, 3 and 4 included 60, 83.3 and 100 % of the cooperative sectors, respectively. In them, the producers owned the land, worked individually and (C3) had higher milk yield. Group 4 was outstanding with 1 833 500 L. It is concluded that, in time, the cooperative sectors C3 separated from C1 and C2. Those groups where the cooperative sectors C1 and C2 predominated had lower amount of animals and milk yield. However, when the percentage of the cooperative sectors C3 increased in the groups, the results were superior, indicating the productive potentialities of the latter. Key words: milk yield, multivariate analysis, cooperative production.